MENGAPA ORANG KATOLIK MASIH MENJALANKAN RITUAL MARAPU? Menguak Praktik Iman Ganda Di Loura - Herman Punda Panda (Jurnal Ledalero, 2014)
The phenomenon of dualism in practising the faith among Catholics who converted from Sumbanese ethnic religion (Marapu) is a real challenge faced by the Catholic Church in Sumba. Such dualism is transparent in the practices of using simultaneously both Catholic and Marapu rites in the popular religiosity of Sumbanese Catholics. Both Catholic priests and Marapu ritual leaders are asked by the people, on different occassions, to perform rituals for their benefit. These two kinds of ritual leaders are equally considered as mediators of communication between human beings and the supernatural world. Such a practice reveals a deep encounter between Catholic and Sumbanese ethnic religion regarding the form, direction and means of communication between humans and supernatural beings. The author’s fieldwork at Weepangali in the district of Sumba Barat Daya, from January to August 2013, reveals a new concept and understanding of mediation, that is a mixture between a Catholic concept and a Marapu one. Some supernatural figures in Marapu religion are equated with those in Catholic devotions. This new understanding, however, is not formally and institutionally recognized in either the Marapu or Catholic hierarchies, but rather found more informally and spontaneously in the religious experience of Sumbanese Catholics. This phenomenon indicates the strong mutual influence between Catholic and Marapu experience, after a prolonged and ongoing encounter. Kata-kata Kunci: Dunia empiris, dunia meta-empiris, ritual Marapu, doktrin Katolik, pengalaman religius, pengantaraan, perjumpaan.